Evaluation of an Amniotic Membrane-Collagen Dermal Substitute in the Management of Full-Thickness Skin Defects in a Pig - Hyunji Kim; Daegu Son; Tae Hyun Choi; Samhyun Jung; Sunyoung Kwon; Junhyung Kim; Kihwan Han (Archives of Plastic Surgery, 2013)
BackgroundTo minimize the inflammatory reaction and improve healing, a new modified dermal substitute composed of an atelocollagen, chondroitin-6-sulfate, and amniotic membrane (AM) was applied to full-thickness skin defects in a pig. Atelocollagen was extracted from bovine skin, and two modified dermal substitutes were generated according to the cross-linking type.MethodsThe AM-collagen dermal substitutes were characterized and compared with currently used dermal substitutes in a pig skin defect model. There were five experimental groups: dehydrothermal (DHT) cross-linking atelocollagen with the AM on the top (AM-DHT), DHT and chemical cross-linking atelocollagen with the AM on the top (AM-DHT/chemical), Terudermis, Integra, and AlloDerm. After 3×3 cm full-thickness skin defects on the back of a pig were created, each dermal substitutes dermal substitutes was randomly grafted on the defects. Two weeks after grafting, autologous partial-thickness skin was over-grafted on the neodermis. The take rate of the dermal substitutes, skin, and histological sections were all assessed at 1, 2, and 4 weeks postoperatively.ResultsMore rapid healing and a higher take rate were evident in the AM-DHT and Terudermis groups. Histological examination revealed fewer inflammatory cells and more fibroblast hyperplasia in these two groups. Four weeks after surgery, the amount of newly formed collagen was significantly more appropriate in the AM-DHT group.ConclusionsThese observations provide supporting evidence that a newly developed amniotic-collagen dermal substitute may inhibit inflammatory reactions and promote wound healing.